Establishing the Infrastructure to Conduct Comparative Effectiveness Research Toward the Elimination of Disparities: A Community-Based Participatory Research Framework - Wilson, Danyell S. (2013)
In Tampa, Florida, researchers have partnered with community- and faith-based organizations to create the Comparative Effectiveness Research for Eliminating Disparities (CERED) infrastructure. Grounded in community-based participatory research, CERED acts on multiple levels of society to enhance informed decision making (IDM) of prostate cancer screening among Black men. CERED investigators combined both comparative effectiveness research and community-based participatory research to design a trial examining the effectiveness of community health workers and a digitally enhanced patient decision aid to support IDM in community settings as compared with “usual care” for prostate cancer screening. In addition, CERED researchers synthesized evidence through the development of systematic literature reviews analyzing the effectiveness of community health workers in changing knowledge, attitudes and behaviors of African American adults toward cancer prevention and education. An additional systematic review analyzed chemoprevention agents for prostate cancer as an emerging technique. Both of these reviews, and the comparative effectiveness trial supporting the IDM process, add to CERED’s goal of providing evidence to eliminate cancer health disparities.